Narratives of Kingship in Eurasian Empires, 1300-1800 - van Leeuwen, Richard (Rulers & Elites, 2017)
An exploration of the constructions of authority in Eurasian empires in fictional texts of various genres, showing remarkable parallels, and the fluidity of literary material as a repository of cultural/political values. Readership: Scholars and students in the fields of history and literature of Eurasian empires, comparative literature, world literature, ideologies of power and authority.